2020
DOI: 10.5194/acp-20-12889-2020
|View full text |Cite
|
Sign up to set email alerts
|

A test of the ability of current bulk optical models to represent the radiative properties of cirrus cloud across the mid- and far-infrared

Abstract: Abstract. Measurements of mid- to far-infrared nadir radiances obtained from the UK Facility for Airborne Atmospheric Measurements (FAAM) BAe 146 aircraft during the Cirrus Coupled Cloud-Radiation Experiment (CIRCCREX) are used to assess the performance of various ice cloud bulk optical property models. Through use of a minimization approach, we find that the simulations can reproduce the observed spectra in the mid-infrared to within measurement uncertainty, but they are unable to simultaneously match the obs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…However, computed scattering properties require ice crystal habit and size distribution assumptions that introduce uncertainty in relating radiances to particle size (Cooper et al, 2006). Prior efforts to evaluate bulk ice cloud scattering properties through the FIR using in situ observations are limited to select case studies (Cox et al, 2010;Bantges et al, 2010) so some refinement of existing particle optical properties may be required.…”
Section: Driversmentioning
confidence: 99%
“…However, computed scattering properties require ice crystal habit and size distribution assumptions that introduce uncertainty in relating radiances to particle size (Cooper et al, 2006). Prior efforts to evaluate bulk ice cloud scattering properties through the FIR using in situ observations are limited to select case studies (Cox et al, 2010;Bantges et al, 2010) so some refinement of existing particle optical properties may be required.…”
Section: Driversmentioning
confidence: 99%
“…TAFTS is a Martin‐Puplett polarizing interferometer (Martin & Puplett, 1969) covering the spectral range of 80–600 cm −1 and has been deployed in numerous airborne field campaigns (e.g., Bantges et al, 2020; Cox et al, 2010; Green et al, 2012). TAFTS uses two sets of liquid helium‐cooled detectors.…”
Section: The Radiation Instrumentation Greenland Flight and Ancillamentioning
confidence: 99%
“…Yi et al 40 , 41 also applied the C6 ice and liquid water cloud models in the broadband radiative transfer models, and achieved better simulation performances in deriving the top of the atmosphere (TOA) cloud radiative effect (CRE) in comparison with Clouds and the Earth’s Radiant Energy System (CERES) observations. Although some studies 42 , 43 found that the C6 ice cloud model exhibited inconsistent performances in the mid and far infrared regions, it generally provided reasonable results for broadband simulations. Apparently, the present status of implementing various kinds of ice cloud optical property parameterizations in remote sensing and modeling studies could induce large uncertainties in the applications 32 .…”
Section: Introductionmentioning
confidence: 96%